sin 8 7 5 ∘ − cos 8 7 5 ∘ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Bonus question: Can you find the exact form of sin ( 7 5 ∘ ) ?
Bonus question: Method 1:
cos ( 1 5 0 ∘ ) = 1 − 2 sin 2 ( 7 5 ∘ )
⟹ sin 2 ( 7 5 ∘ ) = 2 1 ( 1 − cos ( 1 5 0 ∘ ) ) = 2 1 ( 1 + 2 3 ) = 4 1 ( 2 + 3 )
⟹ sin ( 7 5 ∘ ) = 2 2 + 3 ,
where we have taken the positive root as we know that sin ( 7 5 ∘ ) > 0 .
Further, cos ( 7 5 ∘ ) = 1 − sin 2 ( 7 5 ∘ ) = 2 2 − 3 .
Method 2:
sin ( 7 5 ∘ ) = sin ( 3 0 ∘ ) + 4 5 ∘ ) = sin ( 3 0 ∘ ) cos ( 4 5 ∘ ) + cos ( 3 0 ∘ ) sin ( 4 5 ∘ ) =
2 1 × 2 2 + 2 3 × 2 2 = 4 2 + 6 .
Note that ( 2 + 6 ) 2 = 8 + 2 1 2 = 8 + 4 3 = 2 2 + 3 ,
so the two expressions found for sin ( 7 5 ∘ ) are in fact identical.
Great efforts! Nice.
sin 8 7 5 ° − cos 8 7 5 ° = ( sin ( 3 0 ° + 4 5 ° ) ) 8 − ( cos ( 3 0 ° + 4 5 ° ) ) 8 = ( sin 3 0 cos 4 5 + sin 4 5 cos 3 0 ) 8 − ( cos 3 0 cos 4 5 − sin 3 0 sin 4 5 ) 8 = ( 2 1 ⋅ 2 2 + 2 2 ⋅ 2 3 ) 8 − ( 2 3 ⋅ 2 2 − 2 1 ⋅ 2 2 ) 8 = ( 4 2 + 6 ) 8 − ( 4 6 − 2 ) 8 = ( 1 6 8 + 4 3 ) 4 − ( 1 6 8 − 4 3 ) 4 = ( 4 2 + 3 ) 4 − ( 4 2 − 3 ) 4 = ( 1 6 7 + 4 3 ) 2 − ( 1 6 7 − 4 3 ) 2 = ( 2 5 6 9 7 + 5 6 3 ) − ( 2 5 6 9 7 − 5 6 3 ) = 2 5 6 1 1 2 3 = 1 6 7 3 = 0 . 7 5 8 ( 3 d p )
Problem Loading...
Note Loading...
Set Loading...
sin 8 7 5 ∘ − cos 8 7 5 ∘
= ( sin 4 7 5 ∘ − cos 4 7 5 ∘ ) ( sin 4 7 5 ∘ + cos 4 7 5 ∘ )
= ( sin 2 7 5 ∘ − cos 2 7 5 ∘ ) ( sin 2 7 5 ∘ + cos 2 7 5 ∘ ) ( sin 4 7 5 ∘ + cos 4 7 5 ∘ )
= ( sin 2 7 5 ∘ − cos 2 7 5 ∘ ) ( ( sin 2 7 5 ∘ + cos 2 7 5 ∘ ) 2 − 2 sin 2 7 5 ∘ c o s 2 7 5 ∘ )
= ( − cos ( 2 × 7 5 ∘ ) ) ( 1 − 2 sin 2 7 5 ∘ c o s 2 7 5 ∘ )
= − cos 1 5 0 ∘ × ( 1 − 2 sin 2 1 5 0 ∘ )
= − ( 2 3 ) × ( 1 − 8 1 )
= 1 6 7 3 = 0 . 7 5 8 (rounding off up to 3 decimal places)
Identities used :
A 2 − B 2 = ( A + B ) ( A − B ) sin 2 λ + cos 2 λ = 1 sin 2 λ − cos 2 λ = − cos ( 2 ⋅ λ ) 2 ⋅ sin λ ⋅ cos λ = sin ( 2 ⋅ λ )
enjoy !